Kesaksian Wanita Dalam Perspektif Hukum Islam dan Hukum Positif di Indonesia - Mahfiana, Layyin (Sunan Kalijaga State Islamic University & The Asia Foundation, 2009)
The concept of female witness can be seen in two perspectives: first from the Islamic law, and second from a positive law. In the perspective of mainstream Islamic law, most Muslim scholars favor for not giving equal status and rights for women with that of men in acting as witnesses. The inequality is found in the number of male!female witnesses. A male alone can be a witness, while for female needs to be at least two women in order to make their witnesses legally sound. In the Indonesian positive law however, such distinction of number requirement is not found, and therefore a male and or a female can be a witness.